2020
DOI: 10.3390/s20030787
|View full text |Cite
|
Sign up to set email alerts
|

SoilCam: A Fully Automated Minirhizotron using Multispectral Imaging for Root Activity Monitoring

Abstract: A minirhizotron is an in situ root imaging system that captures components of root system architecture dynamics over time. Commercial minirhizotrons are expensive, limited to white-light imaging, and often need human intervention. The implementation of a minirhizotron needs to be low cost, automated, and customizable to be effective and widely adopted. We present a newly designed root imaging system called SoilCam that addresses the above mentioned limitations. The imaging system is multi-modal, i.e., it suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Figure 4 ) from being measured, which is significant because data on genetic variation in early-season rates of above-ground growth have proven very valuable in predicting end-of-season biomass production [ 50 ]. Accelerating the rate of image acquisition could be achieved by: (1) a robot or robots that move around the field visiting minirhizotrons and collecting data, (2) cameras that can acquire images automatically when installed permanently in each minirhizotron, or after being moved from minirhizotron to minirhizotron [ 11 , 39 , 44 ], (3) or by a large team of people using many cameras in parallel. All of these options will require further innovation and/or commercialization to make the necessary equipment available and affordable.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 ) from being measured, which is significant because data on genetic variation in early-season rates of above-ground growth have proven very valuable in predicting end-of-season biomass production [ 50 ]. Accelerating the rate of image acquisition could be achieved by: (1) a robot or robots that move around the field visiting minirhizotrons and collecting data, (2) cameras that can acquire images automatically when installed permanently in each minirhizotron, or after being moved from minirhizotron to minirhizotron [ 11 , 39 , 44 ], (3) or by a large team of people using many cameras in parallel. All of these options will require further innovation and/or commercialization to make the necessary equipment available and affordable.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4) from being measured, which is significant because data on genetic variation in early-season rates of above-ground growth have proven very valuable in predicting end-of-season biomass production (Varela et al 2021). Accelerating the rate of image acquisition could be achieved by: (1) a robot or robots that move around the field visiting minirhizotrons and collecting data; (2) cameras that can acquire images automatically when installed permanently in each minirhizotron, or after being moved from minirhizotron to minirhizotron (Childs et al 2020; Rahman et al 2020; Thomsen and Jensen 2020); (3) or by a large team of people using many cameras in parallel. All of these options will require further innovation and/or commercialization to make the necessary equipment available and affordable.…”
Section: Resultsmentioning
confidence: 99%
“…It is a nondestructive, underground, repetitive process system, which is costly to perform. To overcome this, Rahman et al [ 77 ] designed the SoilCam: a mini rhizotron multispectral imaging system with fully automated functions to perform onsite recording, monitor the plant root growth process, and allow phenotyping research of plants, as shown in Figure 62 .…”
Section: Cmos Image Sensor Applicationsmentioning
confidence: 99%
“… ( a ) Minirhizotron field experiment; ( b ) SoilCam; ( c ) Root and soil analyzer software; ( d ) Control box; ( e ) 360° image captured by SoilCam of a Canola plant root; ( f ) Multispectral images captured by SoilCam [ 77 ]. …”
Section: Figurementioning
confidence: 99%